Cement Manufacturer's Handbook - Peray, Kurt E. (Chemical Publishing Company, Incorporated, 1979)
Annotation This unique handbook contains the most essential engineering formulas used in the cement manufacturing process. All formulas are presented in both English and metric systems of units. Examples are given to familiarize the reader with the usefulness of these formulas. The book can be used as a text manual for courses in cement technology, and as a reference for solving operating problems. The book is equally valuable for the manager supervisor, chemist, and operator as it is to the cement plant engineer.
Keywords: elektronické knihy; electronic books